1999
DOI: 10.1063/1.371517
|View full text |Cite
|
Sign up to set email alerts
|

Photoluminescence study of deep levels in CuGaTe2 crystals

Abstract: A deep photoluminscence band at 0.95 eV was studied in CuGaTe2 crystals. The shape of this band did not change with laser power and no j shift was detected. This band shifts towards higher energy with increasing temperature and its shape becomes more asymmetric. The activation energy of this band was ET=0.20 eV as measured with thermal quenching. The possible association of the 0.95 eV band with grain boundaries or dislocations is discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2001
2001
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 9 publications
1
3
0
Order By: Relevance
“…In the CuGaTe 2 (x ¼1) crystal, two distinct peaks are present at 1.39 and 0.95 eV. The deep level at 0.95 eV has also been observed by Krustok et al [26]. They suggested that the recombination causing the 0.95 eV band originates from the defects, which are segregated near the grain boundaries or dislocations.…”
Section: Photoluminescencesupporting
confidence: 63%
“…In the CuGaTe 2 (x ¼1) crystal, two distinct peaks are present at 1.39 and 0.95 eV. The deep level at 0.95 eV has also been observed by Krustok et al [26]. They suggested that the recombination causing the 0.95 eV band originates from the defects, which are segregated near the grain boundaries or dislocations.…”
Section: Photoluminescencesupporting
confidence: 63%
“…It is well known that PL measurements provide a considerable amount of information about relatively shallow defect levels, but there have been several studies suggest that chalcopyrite structure compounds also contain very deep defect levels, 8,9) which can also be studied using PL spectroscopy. These deep PL bands were recently discovered and studied in CuInSe 2 , 10) CuGaSe 2 , 11) CuAlSe 2 , 12) CuGaTe 2 , 13) and Cu(In,Ga)Se 2 . 14) Therefore, many PL studies have also been performed to characterize CuInS 2 defects.…”
Section: Introductionmentioning
confidence: 76%
“…In contrast, the electronic transport properties of the ABTe 2 compounds are less affected by the detrimental bipolar effect due to their much larger bandgaps on the order of 1 eV. [34,[55][56][57][58][59] More interestingly, we in this work found that the pristine ABTe 2 (A = Cu, Ag; B = Ga, In) chalcopyrites exhibit intrinsic semiconductor to degenerate semiconductor transitions between 700 and 800 K, the origin of which is found to be related to the deep-level in-gap states induced by native A-site vacancies.…”
Section: Ztmentioning
confidence: 99%